ANALISIS PENERAPAN MATEMATIKA PADA ILMU EKONOMI FUNGSI PAJAK DAN SUBSIDI TERHADAP KESEIMBANGAN PASAR - Ahmad Jamiluddin Fikri; Ajeng Afifah Muhartini; Oman Sahroni; Septi Dwi Rahmawati; Tanti Febrianti; Isnaini Mahuda (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2021)
Mathematics is an analytical tool used for problem solving, which is commonly found in business economics. The more time develops, the problem of the economic complex is getting more complex so that it is possible to switch the level of difficulty solving economic problems into solving mathematical problems. Taxes and subsidies are a part of the economy that affects market balance. With taxes, the balance position will change because producers offer higher selling prices. As a result, the market balance formed becomes higher than the balance price before there is tax and the amount of balance will be less. The imposition of taxes and subsidies is very influential for the balance of the market. This study aims to find out the relationship of taxes and subsidies to market balance. The methods used in this research are literature and exploratory studies. The results of research that has been done can be concluded that the influence of both on market balance is opposite or opposite. This can be seen if the factor that is considered fixed changes, then the bid function will change places or shift